2022
DOI: 10.3390/ani12182310
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Genes Occurrence in Conventional and Antibiotic-Free Poultry Farming, Italy

Abstract: Antimicrobial resistance is a complex and widespread problem threatening human and animal health. In poultry farms, a wide distribution of resistant bacteria and their relative genes is described worldwide, including in Italy. In this paper, a comparison of resistance gene distribution in litter samples, recovered from four conventional and four antibiotic-free broiler flocks, was performed to highlight any influence of farming systems on the spreading and maintenance of resistance determinants. Conventional P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Similarly, a more recent work highlighted that the abundance of tetracycline genes was not influenced by the use of grown promoting doses of antimicrobials, even if the aminoglycoside resistance genes tended to be higher in the broiler supplemented with chlortetracycline [ 29 ]. Other studies confirmed that the use of therapeutic doses of antibiotics in poultry farming increases the total ARGs load in intestinal tracts [ 15 ], even if the antibiotic-free farms had a wide distribution of resistant bacteria and related ARGs, as already observed in different geographical areas [ 23 , 42 , 43 ]. Noteworthy, most ARGs, including those investigated in this study, can be located in mobile genetic elements (MGE) as plasmids, trasposons, or insertion sequences, and they are able to move in different microbial niches, conferring the antimicrobial resistance profiles to different bacterial species and allowing for the accumulation and dissemination of resistant microorganisms in the environment [ 44 ].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Similarly, a more recent work highlighted that the abundance of tetracycline genes was not influenced by the use of grown promoting doses of antimicrobials, even if the aminoglycoside resistance genes tended to be higher in the broiler supplemented with chlortetracycline [ 29 ]. Other studies confirmed that the use of therapeutic doses of antibiotics in poultry farming increases the total ARGs load in intestinal tracts [ 15 ], even if the antibiotic-free farms had a wide distribution of resistant bacteria and related ARGs, as already observed in different geographical areas [ 23 , 42 , 43 ]. Noteworthy, most ARGs, including those investigated in this study, can be located in mobile genetic elements (MGE) as plasmids, trasposons, or insertion sequences, and they are able to move in different microbial niches, conferring the antimicrobial resistance profiles to different bacterial species and allowing for the accumulation and dissemination of resistant microorganisms in the environment [ 44 ].…”
Section: Discussionsupporting
confidence: 58%
“…The quantitative polymerase chain reaction (qPCR) was applied to find a panel of ARGs related to the antibiotics commonly used in conventional farming or those critically important in human medicine. Specifically, the target fragments aad A2 for aminoglycosides, tet (A), tet (B), tet (K), and tet (M) for tetracyclines, and mcr -1 for colistin were selected, considering analogous investigations previously carried out in the same area of study [ 23 ]. The above-mentioned fragments were quantified with SYBR Green ® qPCR protocols, as previously described [ 57 , 58 ], using a Magnetic Induction Cycler (Mic) real-time machine (BMS, Australia).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is more expensive than traditional cultivation and does not allow determination of the bacterial sources of resistance genes. However, it is a rapid method that avoids possible underestimation of the occurrence of AMR [ 44 ], as it is able to detect non-culturable or labile bacteria and provides more extensive information on the resistance patterns harboured by all bacteria present in the tested samples and not only those highlighted in selected colonies [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the poultry industry is currently focused on eliminating the use of antibiotics, thus seeking innovative management systems [ 30 ]. The production of antibiotic-free broiler has increased due to consumer perception that poultry meat is qualitatively superior to conventionally produced meat [ 31 , 32 ]. Alternative methods to antibiotics for the control of bacterial diseases in poultry farms could be natural substances such as some essential oils that, due to their potential antimicrobial properties, could find application in poultry phytotherapy [ 33 ].…”
Section: Introductionmentioning
confidence: 99%